The implementation of Problem Based Learning model to Improve Students Achievement on Economics Subject, Class in Grade 2 of IPS XI at SMA Negeri 2 Gorontalo Utara - Melizubaida Mahmud (AIBPM Publisher, 2018)
This Research aimed to improve students learning outcomes on economic subjects by using the problem-based learning models in grade 2 of IPS XI at SMA Negeri 2 Gorontalo Utara. The research method used is Classroom Action Research (CAR), with sample of 25 students. Based on the results, the implementation of classroom action research consists of 2 cycles, i.e., the cycle I and II. The results of the analysis in the first cycle showed that students mastery learning was subjected to the action of 25 students, there were 10 students (40%) scored 75 while 15 students (60%) scored 75 with an average score of 73, 6. The percentage of completeness increased in the second cycle, 25 students who were subjected to actions that achieved completeness were 21 students (84%) obtained score 75 and the remaining 4 people (16%) scored less than < 75 with an average score of 80 % and 4 students who have not reached completeness are given a remedial with the aim that their learning outcomes can achieve completeness. Keywords: Problem-Based Learning Model, Students Learning Outcomes